A SSZ-13 molecular sieve and its preparation method and application

By activating natural silicon-aluminum minerals and mechanical treatment, combining the coordinated induction method of alkali source and water, SSZ-13 molecular sieve was prepared, which solved the problems of high cost and environmental pollution in traditional methods, and achieved efficient CO2/CH4 separation and NOx detachment. Removal effect.

CN117342578BActive Publication Date: 2025-01-17CHINA UNIV OF PETROLEUM (BEIJING)
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311140398.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-05
Publication Date
2025-01-17
Estimated Expiration
2043-09-05

AI Technical Summary

Technical Problem

The existing SSZ-13 molecular sieve synthesis method uses expensive N,N,N-trimethyldamantane ammonium hydroxide (TMADaOH) as the template agent, resulting in high cost and environmental pollution, and traditional methods require high temperature roasting, and crystal seeds The amount of addition cannot effectively reduce costs.

Method used

By activate natural silicon-aluminum minerals using the first alkali source and mechanically treating them with the SSZ-13 seeds, a synergistic induction effect is formed, and the use of silicon, aluminum chemical reagents and SSZ-13 seeds is reduced, and a mixed alkali and silicon source is used. , mix water, aging and crystallization treatment, prepare SSZ-13 molecular sieve, avoiding the use of TMADaOH and high-temperature roasting.

Benefits of technology

It significantly reduces the synthesis cost of SSZ-13 molecular sieve, improves the crystallinity, and realizes the CO2/CH4 separation selectivity and the efficient performance of the NOx remover of automobile exhaust, which has environmental protection and economical advantages.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117342578B_ABST
    Figure CN117342578B_ABST
Patent Text Reader

Abstract

The present invention provides an SSZ-13 molecular sieve and a preparation method and application thereof. The method uses a first alkali source including sodium hydroxide, potassium hydroxide and / or cesium hydroxide to activate natural silica-alumina minerals, then adds SSZ-13 seed crystals for mechanical treatment, then adds a silicon source, a second alkali source and water to obtain a reactant gel, and the reactant gel is subjected to aging treatment and crystallization treatment in sequence to obtain an SSZ-13 molecular sieve. The amount of silica-alumina chemical reagents and SSZ-13 seed crystals can be reduced, and TMADaOH can be omitted, which effectively reduces costs and is more environmentally friendly. The SSZ-13 molecular sieve prepared by the method is used for CO 2 / CH 4 During adsorption separation, it has a high separation selectivity; automobile exhaust NO can be obtained by copper ion exchange on the SSZ-13 molecular sieve. x Remover, the NO x The remover has a wider active window temperature and higher nitrogen selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to chemical synthesis technology and its application field, and in particular to an SSZ-13 molecular sieve and its preparation method and application. Background Art

[0002] SSZ-13 molecular sieve has a chabazite (CHA) topological structure, which is composed of silicon-oxygen and aluminum-oxygen tetrahedrons connected end to end through oxygen atoms, orderly arranged into a crystal structure with eight-membered ring channels and three-dimensional cross channels. It belongs to a small-pore molecular sieve with a pore size of 0.38nm×0.38nm and a specific surface area of ​​up to 700m 2 / g, it has good hydrothermal stability, acidity adjustability, ion exchangeability, high activity and high selectivity, and has broad application prospects.

[0003] At present, N,N,N-trimethyladamantane ammonium hydroxide (TMADaOH) is usually used as a template agent when synthesizing SSZ-13 molecular sieves. However, TMADaOH is expensive and the dosage is large, and it increases with the increase of the silicon-aluminum ratio of the feed. When the synthetic silicon-aluminum ratio is lower than 40, the amount of template agent (Na2O / SiO2) is usually greater than 0.1, and when the silicon-aluminum ratio exceeds 40, the amount of template agent is higher, resulting in high cost of synthetic raw materials, and this method needs to be calcined at above 500°C to remove the template agent, which has high energy consumption, further resulting in high cost of synthesizing SSZ-13 molecular sieves; at the same time, toxic and harmful gases such as nitrogen oxides are also produced during calcination, causing environmental pollution.

[0004] Based on this, the document (Microporous and Mesoporous Materials, 2014, 196: 341-348) reported a method for synthesizing SSZ-13 molecular sieves by seed crystals. The method synthesized SSZ-13 molecular sieves by adding SSZ-13 seed crystals, which can avoid or reduce the addition of TMADaOH template agent, and thus can also avoid high-temperature roasting. However, the amount of SSZ-13 seed crystals added is 20% of the total mass of the silicon source, which is a large amount, resulting in high synthesis costs and insignificant cost reduction effects.

[0005] Therefore, it is of great significance to develop an economical and environmentally friendly method for synthesizing SSZ-13 molecular sieve. Summary of the invention

[0006] The invention provides a method for preparing SSZ-13 molecular sieve, which can synthesize SSZ-13 molecular sieve under the conditions of no TMADaOH and low SSZ-13 seed addition, while reducing the amount of silicon and aluminum chemical reagents used, reducing the synthesis cost, and being more environmentally friendly.

[0007] The present invention also provides a SSZ-13 molecular sieve which is prepared by the above preparation method and has high crystallinity.

[0008] The present invention further provides a CO2 / CH4 separation agent, comprising the above-mentioned SSZ-13 molecular sieve, which has a higher CO2 / CH4 separation selectivity.

[0009] The invention also provides an automobile exhaust NO x The removal agent is obtained by copper ion exchange of the SSZ-13 molecular sieve according to claim 8, wherein the NO x The remover has a wider active window temperature and higher nitrogen selectivity.

[0010] The present invention provides a method for preparing SSZ-13 molecular sieve, comprising the following steps:

[0011] 1) activating the natural silica-aluminum mineral using a first alkali source to obtain an activated natural silica-aluminum mineral;

[0012] 2) adding SSZ-13 seed crystals to the activated natural silica-alumina mineral to obtain a first mixture, and mechanically treating the first mixture to obtain a second mixture; wherein the crystallinity of the SSZ-13 seed crystals in the second mixture is 30% to 80% of the crystallinity of the SSZ-13 seed crystals in the first mixture;

[0013] 3) mixing the second mixture with a silicon source, a second alkali source and water to obtain a reactant gel;

[0014] 4) subjecting the reactant gel to aging treatment and crystallization treatment in sequence to obtain SSZ-13 molecular sieve;

[0015] Wherein, the contents of active silicon and active aluminum in the activated natural silica-aluminum mineral are not less than 90wt% of the silicon source and aluminum source in the natural silica-aluminum mineral respectively;

[0016] The first alkali source and the second alkali source include sodium hydroxide, potassium hydroxide and / or cesium hydroxide;

[0017] In the first alkali source, the molar ratio of sodium hydroxide to the first alkali source is (0.2-0.9):1; in the second alkali source, the molar ratio of sodium hydroxide to the second alkali source is (0.5-0.92):1;

[0018] The mass ratio of the SSZ-13 seed crystal to the silicon source is (0.1-10.0):100;

[0019] In the reactant gel, the molar ratio of the alkali source, the silicon source, the aluminum source and water is (7.0-15.5): (10-120): 1: (1600-2200).

[0020] According to one embodiment of the present invention, in step 1), the mass ratio of the first alkali source to the natural silica-alumina mineral is (1.2-1.8):1; and / or,

[0021] In the first alkali source, the molar ratio of sodium hydroxide to the first alkali source is (0.6-0.9):1.

[0022] According to one embodiment of the present invention, the mass ratio of the SSZ-13 seed crystal to the silicon source is (0.1-3.0):100.

[0023] According to one embodiment of the present invention, step 3) further comprises adding TMAdaOH to the system comprising the second mixture, a silicon source, an alkali source and water, wherein the molar ratio of the TMAdaOH to the silicon source is (0-0.01):1.

[0024] According to one embodiment of the present invention, in step 2), the mechanical treatment includes a first mechanical treatment and a second mechanical treatment, and the first mechanical treatment includes a pulverizing treatment;

[0025] The second mechanical treatment includes at least one of grinding, mechanical ball milling, mechanical kneading, and extrusion molding, and when the second mechanical treatment includes the mechanical kneading and / or the extrusion molding, water is added to the first mixture, and the mass ratio of the water to the first mixture is (5-20):100.

[0026] According to one embodiment of the present invention, the size of the activated natural silica-alumina mineral is less than 200 mesh; and / or,

[0027] The second mixture has a size of less than 200 mesh.

[0028] According to one embodiment of the present invention, the aging treatment temperature is 50-70° C. and the time is 2-8 hours; and / or,

[0029] The crystallization treatment is dynamic crystallization, and the temperature of the dynamic crystallization is 150-180° C. and the time is 12-72 hours.

[0030] The present invention also provides a SSZ-13 molecular sieve, which is prepared by any of the above methods.

[0031] The present invention further provides a CO2 / CH4 separation agent, comprising the aforementioned SSZ-13 molecular sieve.

[0032] The invention also provides an automobile exhaust NO x The removing agent is obtained by exchanging the aforementioned SSZ-13 molecular sieve with copper ions.

[0033] The present invention activates natural silica-alumina minerals by using a mixed alkali source including sodium hydroxide, potassium hydroxide and / or cesium hydroxide, and then mixes the activated natural silica-alumina minerals with SSZ-13 seed crystals for mechanical treatment, and utilizes the synergistic induction effect generated by the mixed alkali source, the activated natural silica-alumina minerals and the SSZ-13 seed crystals to prepare the SSZ-13 molecular sieve, which can reduce the amount of silicon, aluminum chemical reagents and SSZ-13 seed crystals used in the preparation process, and does not need to use TMADaOH, effectively reducing the preparation cost. The SSZ-13 molecular sieve prepared by the method has a high crystallinity. When the SSZ-13 molecular sieve is used for CO2 / CH4 adsorption separation, it has a high CO2 / CH4 separation selectivity. The SSZ-13 molecular sieve can be used to purify nitrogen oxides in automobile exhaust after copper ion exchange, and has a wide active window temperature and high nitrogen selectivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 is a schematic diagram of the process of preparing SSZ-13 molecular sieves in Examples 1-14;

[0035] Figure 2a is the XRD spectra of the molecular sieves obtained in Examples 1-14 and Comparative Example 9;

[0036] Figure 2b is the XRD spectrum of the molecular sieve obtained in Comparative Examples 1-10;

[0037] Figure 3a is a SEM image of the SSZ-13 molecular sieve obtained in Example 1;

[0038] Figure 3b is a SEM image of the molecular sieve obtained in Comparative Example 1;

[0039] Figure 3c This is a SEM image of the molecular sieve obtained in Comparative Example 2;

[0040] Figure 3d This is a SEM image of the molecular sieve obtained in Comparative Example 3;

[0041] Figure 4a is the nitrogen isotherm adsorption curve of the SSZ-13 molecular sieve obtained in Example 3;

[0042] Figure 4b is the nitrogen isotherm adsorption curve of the SSZ-13 molecular sieve obtained in Example 10;

[0043] Figure 5 The SSZ-13 molecular sieve obtained in Example 1 is used for CO2 / CH4 gas separation test results;

[0044] Figure 6ais the conversion rate of NO when the SSZ-13 molecular sieve obtained in Example 1 is used for NH3-SCR;

[0045] Figure 6b The SSZ-13 molecular sieve obtained in Example 1 has N2 selectivity when used for NH3-SCR. DETAILED DESCRIPTION

[0046] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific implementation methods listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0047] The first aspect of the present invention provides a method for preparing SSZ-13 molecular sieve, comprising the following steps:

[0048] 1) activating the natural silica-aluminum mineral using a first alkali source to obtain an activated natural silica-aluminum mineral;

[0049] 2) adding SSZ-13 seed crystals to the activated natural silica-alumina mineral to obtain a first mixture, and mechanically treating the first mixture to obtain a second mixture; wherein the crystallinity of the SSZ-13 seed crystals in the second mixture is 30% to 80% of the crystallinity of the SSZ-13 seed crystals in the first mixture;

[0050] 3) mixing the second mixture with a silicon source, a second alkali source and water to obtain a reactant gel;

[0051] 4) subjecting the reactant gel to aging treatment and crystallization treatment in sequence to obtain SSZ-13 molecular sieve;

[0052] The contents of active silicon and active aluminum in the activated natural silica-aluminum mineral are not less than 90 wt% of the silicon source and aluminum source in the natural silica-aluminum mineral, respectively.

[0053] The first alkali source and the second alkali source include sodium hydroxide, potassium hydroxide and / or cesium hydroxide;

[0054] In the first alkali source, the molar ratio of sodium hydroxide to the first alkali source is (0.2-0.9):1;

[0055] In the second alkali source, the molar ratio of sodium hydroxide to the second alkali source is (0.5-0.92):1;

[0056] The mass ratio of SSZ-13 seed crystal to the silicon source is (0.1-10.0):100;

[0057] In the reactant gel, the molar ratio of the alkali source, the silicon source, the aluminum source and water is (7.0-15.5):(10-120):1:(1600-2200).

[0058] It should be explained that the above-mentioned natural silica-aluminum minerals include at least one of kaolin, metakaolin, rectorite, attapulgite, bentonite and montmorillonite. The present invention does not limit the specific content of the silicon source and the aluminum source in the above-mentioned natural silica-aluminum minerals. In some specific implementation processes, the SiO2 content of kaolin is 50.5wt.%, and the Al2O3 content is 44.6wt.%; metakaolin is obtained by dehydrating kaolin; the SiO2 content of rectorite is 43.3wt.%, and the Al2O3 content is 37.1wt.%; the SiO2 content of attapulgite is 52.2wt.%, and the Al2O3 content is 13.7wt.%; the SiO2 content of bentonite is 68.2wt.%, and the Al2O3 content is 10.7wt.%; the SiO2 content of montmorillonite is 58.6wt.%, and the Al2O3 content is 14.3wt.%. Since kaolin, rectorite and bentonite are cheap and readily available, have a stable silicon-aluminum ratio and a low impurity content, in specific implementation, it is preferred that the natural silicon-aluminum mineral is at least one of kaolin, rectorite and bentonite.

[0059] The above-mentioned active silicon and active aluminum specifically refer to silicon-aluminum species that can be extracted from natural silicon-aluminum minerals after activation by acid or alkaline solutions and can provide silicon sources and aluminum sources for the synthesis of molecular sieves.

[0060] In step 3), the reactant gel is obtained by mixing and stirring the second mixture, the silicon source, the second alkali source and water, wherein the silicon source comprises at least one of white carbon black, silica sol, silica gel and diatomaceous earth. Considering the crystallinity of SSZ-13 molecular sieve, white carbon black and silica gel are preferred; the second alkali source and the first alkali source may be the same or different, preferably the same.

[0061] In step 4), after the crystallization treatment is completed, the crystallized product is sequentially cooled, washed and dried to obtain the SSZ-13 molecular sieve.

[0062] In the above-mentioned first alkali source and second alkali source, the molar ratio of sodium hydroxide to the alkali source is calculated as Na2O and MOH (total molar number of alkali); the molar ratio of SSZ-13 seed crystals to the silicon source is calculated as SiO2; the molar ratio of the alkali source, silicon source, aluminum source and water is calculated as M2O, SiO2, Al2O3 and H2O.

[0063] The activation treatment process of the present invention is a process of converting crystalline natural silica-alumina minerals into highly active oligomeric silica-alumina species; the mechanical treatment is a process of uniformly mixing the activated natural silica-alumina minerals with the SSZ-13 molecular sieve and generating silicon-oxygen-aluminum and silicon-oxygen-silicon bonds; the reactant gel is a precursor solution of the SSZ-13 molecular sieve; during the aging treatment process, the oligomeric silica-alumina species are directly converted in situ into secondary structural units and nucleation precursors under the guidance of alkali metal cations and the SSZ-13 molecular sieve; during the crystallization treatment process, the nucleation precursor grows to obtain the SSZ-13 molecular sieve.

[0064] The inventors found that after using a mixed alkali source to activate natural silica-alumina minerals, highly active oligomeric silica-alumina species can be obtained; during mechanical treatment, the mixed alkali source produces hydroxyl groups on the molecules of the SSZ-13 seed crystals, which can produce bonding with highly active silica-alumina species, thereby enabling the activated natural silica-alumina minerals and SSZ-13 seed crystals to synergistically induce SSZ-13 nucleation; in addition, the mixed alkali source also has the effect of inducing the activated natural silica-alumina minerals to transform into SSZ-13 molecular sieve secondary structural units and nucleation precursors. Therefore, the present invention can synthesize SSZ-13 molecular sieves with higher crystallinity under the conditions of less than 10% silicon source and no TMAdaOH in the amount of seed crystals, significantly reducing the synthesis cost of SSZ-13 molecular sieves.

[0065] At the same time, the aluminum in the activated natural silica-alumina mineral completely serves as the aluminum source in the synthesis process of the SSZ-13 molecular sieve, and the silicon in the activated natural silica-alumina mineral serves as the silicon source for part of the synthesis of the SSZ-13 molecular sieve. Therefore, the present invention can reduce the use of high-purity silicon and aluminum chemical reagents prepared by complex chemical reactions and separation processes; when diatomaceous earth (natural silica-alumina mineral) is selected as the silicon source in step 3), the use of silicon chemical reagents can be avoided, further reducing the synthesis cost of the SSZ-13 molecular sieve, and it is more environmentally friendly.

[0066] It is worth mentioning that the SSZ-13 molecular sieve prepared by the present invention uses sodium ions, potassium ions and / or cesium ions as alkali sources to prepare the SSZ-13 molecular sieve. Compared with the traditional method of obtaining the SSZ-13 molecular sieve loaded with potassium ions and cesium ions by ion exchange of the synthesized Na-SSZ-13, the SSZ-13 molecular sieve of the present invention has a larger potassium ion and cesium ion loading capacity because the alkali metal cations are directly converted in situ into the final evolution product, and by controlling the ratio of the alkali metal cations of the alkali source during the activation process of natural silica-alumina minerals, the location and density of potassium ions and cesium ions can be controlled, and the gating effect of potassium ions and cesium ions can be fully exerted. Therefore, when the SSZ-13 molecular sieve prepared by the present invention is used for the selective separation of CO2 / CH4, when 1g of SSZ-13 molecular sieve is used as the CO2 / CH4 separation agent, the CH4 penetration time is extremely short, and the CO2 penetration time is as long as 1500 seconds, which shows that the synthesized SSZ-13 can achieve efficient separation of CO2 and CH4 gases.

[0067] Furthermore, the SSZ-13 molecular sieve synthesized by the present invention can also be used as a NOx remover for automobile exhaust after ion exchange with copper ions. x The remover is used for ammonia selective catalytic reduction reaction (NH3-SCR), and at 150-600°C, the NO conversion rate is not less than 80%, the nitrogen selectivity is not less than 90%, and it shows a wide active window temperature and high nitrogen selectivity.

[0068] It should be noted that when a single alkali source is selected to activate natural silica-alumina minerals, a pure phase SSZ-13 molecular sieve cannot be obtained, while when a mixed alkali source is used to activate natural silica-alumina minerals, a pure phase SSZ-13 molecular sieve can be obtained. The amount of sodium hydroxide in the first alkali source and the second alkali source will also affect the synthesis of the SSZ-13 molecular sieve. When the amount of sodium hydroxide in the first alkali source is too small, the natural silica-alumina mineral activation product cannot be converted into a SSZ-13 nucleation secondary structural unit during aging and crystallization. When the content of sodium hydroxide in the second alkali source is too small, the SSZ-13 molecular sieve cannot be synthesized or the obtained product is a SSZ-13 molecular sieve containing other impurities. Therefore, the present invention controls the molar ratio of sodium hydroxide to the first alkali source in the first alkali source to be (0.2-0.9):1; in the second alkali source, the molar ratio of sodium hydroxide to the second alkali source is (0.5-0.92):1.

[0069] The content of the above-mentioned active silicon and active aluminum is measured by an inductively coupled plasma spectrometer (ICP). Specifically: the activated natural silica-alumina mineral is dissolved in a 0.1 mol / L dilute hydrochloric acid solution and then an ICP test is performed. When the content of active silicon and active aluminum is lower than this range, the natural silica-alumina mineral will not be fully activated, and the unactivated natural silica-alumina mineral will be transferred in situ to the final crystallization product SSZ-13 molecular sieve, resulting in the resultant product not being a pure phase SSZ-13 molecular sieve. Therefore, the content of active silicon and active aluminum in the activated natural silica-alumina mineral obtained in the control step 1) of the present invention is greater than 90% of the silicon source and aluminum source content in the natural silica-alumina mineral.

[0070] In step 2), when activated natural silica-aluminum minerals and SSZ-13 seeds are simultaneously present in the synthesis system of SSZ-13 molecular sieve, the two will act as independent induced nucleation units, and a competitive nucleation effect will occur, which cannot guide the generation of SSZ-13 molecular sieves. Therefore, the present invention combines activated natural silica-aluminum minerals and SSZ-13 seeds together through a mechanical treatment method, avoiding competitive nucleation between the two, and can exert the synergistic induction effect of activated natural silica-aluminum minerals and SSZ-13 seeds on SSZ-13 molecular sieves. During the mechanical treatment process, when the crystallinity of the SSZ-13 seeds in the second mixture is 30% to 80% of the crystallinity of the SSZ-13 seeds in the first mixture, and characterized by infrared spectroscopy and Raman spectroscopy, new bonds belonging to silicon-oxygen aluminum or silicon-oxygen silicon appear in the spectrum of the second mixture. It shows that the activated natural silica-aluminum minerals are fully mixed with the SSZ-13 seeds and form good bonding. In specific implementation, the crystallinity of the SSZ-13 seeds in the first mixture and the second mixture can be characterized and calculated by an X-ray diffractometer.

[0071] In the present invention, controlling the molar ratio of the alkali source, silicon source, aluminum source and water in the reactant gel to be (7.0-15.5): (10-120): 1: (1600-2200) is also a key factor in synthesizing the SSZ-13 molecular sieve. When the amount of the alkali source is too much, the pH of the synthetic gel will deviate from the SSZ-13 molecular sieve synthesis interval, reduce the silicon source utilization rate and product yield, etc., which is not conducive to the synthesis of the SSZ-13 molecular sieve, and is not conducive to the operation of the equipment, unsafe and environmentally friendly, while when the alkali source content is too little, the SSZ-13 molecular sieve cannot be synthesized.

[0072] In the specific preparation process, when different natural silica-alumina minerals are selected, there are differences in the content of silicon source and aluminum source in the activated natural silica-alumina minerals. The present invention calculates the amount of other raw materials required for synthesizing SSZ-13 molecular sieve based on the amount of aluminum source in the activated natural silica-alumina mineral. The missing silicon source and alkali source are supplemented in step 3), and the amount added is calculated based on the molar ratio of the alkali source, silicon source, aluminum source and water.

[0073] The present invention does not limit the activation treatment method in step 1), and it can be achieved by alkali fusion activation method, sub-molten salt activation method and pseudo-solid phase activation method. For economic considerations (energy consumption, material consumption, etc.), sub-molten salt activation method and pseudo-solid phase activation method are preferred. In specific implementation, when the alkali fusion activation method is selected, it includes: mixing the first alkali source with the natural silica-aluminum mineral and placing it in a high-temperature muffle furnace for roasting for 5-8 hours, setting the temperature to exceed the melting point of the alkali by 10°C, and obtaining an alkali fusion activation product after roasting; when the sub-molten salt activation method is selected, it includes: configuring the first alkali source and water into an alkali solution in a mass ratio of 1:5-10, then adding natural silica-aluminum minerals, stirring continuously for 5 minutes to form a suspension, and placing the suspension at 200-300°C for activation treatment for 2-5 hours to obtain a sub-molten salt activation product. When the pseudo-solid phase activation method is selected, it includes: mixing natural silica-aluminum minerals and a first alkali source, placing the mixture in a pulverizer and treating it for 2 minutes at an output power of 800W and a rotation speed of 26000r / min to obtain an alkaline earth mixture, adding water equivalent to 8-17wt% of the total mass of the solid to the alkaline earth mixture, stirring and mixing evenly, placing it in an extruder for kneading, and then extruding to obtain wet strips with a diameter of 1.5-2.0mm, placing the wet strips at 150°C for 3-6h to obtain a pseudo-solid phase activation product.

[0074] When the mass ratio of the first alkali source to the natural silica-alumina mineral in the control step 1) is (1.2-1.8): 1, the activation treatment of the natural silica-alumina mineral can be achieved. When the alkali source content is too much, the viscosity of the activation system will increase, the fluidity will decrease, the mass transfer and activation effects will decrease, and the activation system will become too corrosive. When the alkali source content is too little, the activated natural silica-alumina mineral will not be fully activated, and the content of active silicon and active aluminum contained therein will be low, which is not conducive to the formation of SSZ-13 molecular sieve.

[0075] Furthermore, when the molar ratio of sodium hydroxide to the first alkali source in the first alkali source is controlled to be (0.6-0.9): 1, the natural silica-alumina mineral can be completely activated, and the ratio of different alkali metal cations in the activated natural silica-alumina mineral is in a range that is conducive to guiding the nucleation and growth of the SSZ-13 molecular sieve, thereby obtaining a SSZ-13 molecular sieve with higher crystallinity.

[0076] According to the inventors' research, when the mass ratio of SSZ-13 seed crystals to silicon source is (0.1-3.0):100, that is, when the amount of SSZ-13 seed crystals used is extremely small, SSZ-13 molecular sieves with high crystallinity can also be prepared, which can greatly reduce the preparation cost of SSZ-13 molecular sieves.

[0077] In the present invention, step 3) further comprises adding TMAdaOH to the system comprising the second mixture, the silicon source, the alkali source and water, wherein the molar ratio of TMAdaOH to the silicon source is (0-0.01):1.

[0078] According to research, the present invention can synthesize SSZ-13 molecular sieve without TMAdaOH. In addition, the inventors also found that when preparing the reactant gel, adding a trace amount of TMAdaOH can further improve the crystallinity of the SSZ-13 molecular sieve.

[0079] Generally, the amount of TMAdaOH added is determined according to the silicon-aluminum ratio of the reactant gel. The system with a higher silicon-aluminum ratio is more difficult to synthesize, and a larger amount of TMAdaOH is required. In the present invention, the silicon-aluminum ratio of the reactant gel obtained by the above method ranges from SiO2 / Al2O3=10-120. Within this range, the molar ratio of TMAdaOH to the silicon source is (0-0.01) in terms of SiO2: 1, preferably T / SiO2=0.005. The inventor can of course also appropriately adjust the amount of TMAdaOH added according to the actual silicon-aluminum ratio of the reactant gel. It should be noted that the amount of TMAdaOH is obtained by minimizing the amount of TMAdaOH while ensuring the crystallinity of the SSZ-13 molecular sieve. When the amount of TMAdaOH is increased, the SSZ-13 molecular sieve can still be obtained.

[0080] In the above step 2), the mechanical treatment includes a first mechanical treatment and a second mechanical treatment, the first mechanical treatment includes a crushing treatment; the second mechanical treatment includes at least one of grinding, mechanical ball milling, mechanical kneading, and extrusion molding, and when the second mechanical treatment includes the mechanical kneading and / or extrusion molding, water is added to the first mixture, and the mass ratio of water to the first mixture is (5-20):100.

[0081] Among them, pulverization refers to mixing and crushing the first mixture by using shear force, collision force, friction force, etc.; grinding, mechanical ball milling, mechanical kneading and extrusion molding refer to mixing and crushing the first mixture by using mechanical forces such as collision force, extrusion force, shear force and friction force.

[0082] Due to the presence of mechanical forces such as extrusion force and shear force in the second mechanical treatment, the first mixture contains activated natural silica-alumina minerals that are easy to agglomerate. If they are not well pre-mixed with SSZ-13 seed crystals, they are easy to agglomerate during the treatment process, which is not conducive to obtaining a uniform and well-bonded second mixture. However, this phenomenon can be avoided by performing the second mechanical treatment after the pulverization treatment. After the pulverization treatment, the particle size of the activated natural silica-alumina minerals and SSZ-13 seed crystals is reduced, and the two are mixed more evenly, so they are not easy to agglomerate. In addition, due to the reduction in the particle size of the first mixture, the activated natural silica-alumina minerals and SSZ-13 seed crystals can form a good bond.

[0083] When mechanical kneading and / or extrusion molding is selected, since the operating conditions of mechanical molding need to be met, that is, the processing process needs to maintain a certain mechanical force and lubricity, a certain amount of water needs to be added during the processing to generate appropriate mechanical force and at the same time enable the activated natural silica-alumina mineral and SSZ-13 seed crystals to produce better bonding.

[0084] The present invention does not limit the above-mentioned mechanical treatment method. For example, the pulverization treatment can be achieved by a blade crusher, a hammer crusher, a crusher, etc.; the grinding treatment can be achieved by manual grinding, vertical powder grinding machine grinding, etc.; mechanical ball milling can be achieved by a planetary ball mill; mechanical mixing and extrusion molding can be achieved by a twin-screw extruder.

[0085] It has been found that when the size of the activated natural silica-alumina mineral is less than 200 mesh, it can form a better bonding interaction with the SSZ-13 molecular sieve when used for mechanical treatment in step 2), thereby facilitating the preparation of the SSZ-13 molecular sieve. The present invention does not limit the method of processing the activated natural silica-alumina mineral to a size less than 200 mesh, and illustratively, it can be achieved by crushing and screening.

[0086] Furthermore, when the size of the second mixture is controlled to be less than 200 mesh, it is beneficial to reduce the concentration gradient inside and outside the second mixture particles, accelerate the nucleation rate, and then promote the generation of SSZ-13 molecular sieve nucleation precursor. At the same time, the size of the second mixture affects the size of the prepared molecular sieve. When its size is less than 200 mesh, the prepared SSZ-13 molecular sieve particles are small and uniform in size.

[0087] In step 4), the aging treatment temperature is 50-70°C and the time is 2-8h, preferably aging at 60°C for 4h.

[0088] The aging treatment of the present invention is carried out under stirring, which can be achieved through a one-step aging treatment or through a first aging treatment and a second aging treatment. When the first aging treatment and the second aging treatment are used, TMAdaOH and the silicon source are added after the first aging treatment and before the second aging treatment. The first aging treatment is used to evenly disperse the second mixture in the liquid phase and convert the second mixture into SSZ-13 nucleation secondary structural units in situ. The second aging treatment is used for aging the synthetic gel to convert the synthetic gel into a more uniform molecular sieve synthesis precursor. Compared with the one-step aging treatment, the two-step aging treatment is beneficial to obtain a homogeneous SSZ-13 molecular sieve and improve the crystallinity of the SSZ-13 molecular sieve.

[0089] The crystallization treatment of the present invention is dynamic crystallization, and the temperature of the dynamic crystallization is 150-180° C. and the time is 12-72 hours. Considering the crystal phase purity and crystallinity and the synthesis cost, the crystallization temperature and time are preferably 160-170° C. for 18-24 hours, and more preferably 170° C. for 18-24 hours.

[0090] When the crystallization temperature is too low, the crystallization time needs to be extended to form crystals, while when the crystallization temperature is too high, MOR impurity phase (mordenite) is easily generated, which is not conducive to obtaining pure phase SSZ-13 molecular sieve.

[0091] The second aspect of the present invention provides a SSZ-13 molecular sieve, which is prepared by any of the aforementioned methods, and the SSZ-13 molecular sieve has a high degree of crystallinity.

[0092] The third aspect of the present invention provides a CO2 / CH4 separation agent, comprising the aforementioned SSZ-13 molecular sieve. The CO2 / CH4 separation agent has a high CO2 / CH4 separation selectivity.

[0093] A fourth aspect of the present invention provides an automobile exhaust NO x The removal agent is obtained by exchanging the aforementioned SSZ-13 molecular sieve with copper ions. During the copper ion exchange process, the sodium ions, potassium ions and / or cesium ions in the SSZ-13 molecular sieve are replaced by copper ions. x The remover has high activity in the temperature range of 150-600°C, with a NO conversion rate of more than 80% and a N2 selectivity of more than 98%.

[0094] It should be noted that the present invention does not limit the specific method of ion exchange. For example, SSZ-13 molecular sieve and copper sulfate solution can be mixed at a solid-liquid ratio of 1:20 (mass ratio) and then ion exchanged at 80°C for 2h, then washed with deionized water until neutral, dried at 110°C, and calcined at 550°C for 2h to obtain automobile exhaust NO x Remover.

[0095] The present invention is described in more detail below through specific examples.

[0096] The flow charts of Examples 1-14 of the present invention are as follows Figure 1 shown.

[0097] Example 1

[0098] 1) Preparation of activated natural silica-alumina minerals

[0099] Sodium hydroxide and potassium hydroxide are used as the first alkali source, and kaolin is activated by a sub-molten salt activation method. The specific steps are: 8.0g of sodium hydroxide, 5.9g of potassium hydroxide, and 60g of deionized water are mixed and added into a polytetrafluoroethylene activation kettle, 10g of kaolin is added under stirring, and the activation kettle is placed in an oven at 250°C for activation for 3h to obtain activated kaolin; the activated kaolin is crushed and sieved to less than 200 meshes;

[0100] The molar ratio of sodium hydroxide to the first alkali source is 0.66:1; the mass ratio of the first alkali source to kaolin is 1.39:1; the contents of active silicon and active aluminum in the activated kaolin are 93wt% and 95wt% of the silicon source and aluminum source in natural silica-alumina minerals, respectively;

[0101] 2) Preparation of the second mixture

[0102] 9.8 g of activated kaolin and 1.1 g of SSZ-13 seed crystals were mixed to obtain a first mixture; the first mixture was crushed in a crusher for 2 min (output power 800 W, speed 26000 r / min), and then ball-milled in a ball mill at a speed of 300 rpm for 60 min to obtain a second mixture; the second mixture was crushed and sieved to less than 200 mesh;

[0103] wherein the crystallinity of the SSZ-13 seed crystals in the second mixture is 67% of the SSZ-13 seed crystals in the first mixture;

[0104] 3) Preparation of reactant gel

[0105] Using sodium hydroxide and potassium hydroxide as the second alkali source, 0.38 g of sodium hydroxide and 0.18 g of potassium hydroxide were dissolved in deionized water under stirring, and then the second mixture was added, and the mixture was aged at 60° C. for 2 h, and then white carbon black was added, and the mixture was aged at 60° C. for 4 h to obtain a reactant gel;

[0106] The molar ratio of sodium hydroxide to the second alkali source is 0.75:1; the total molar ratio of the alkali source, silicon source, aluminum source and water in the reactant gel is 7:20:1:1800; the mass ratio of SSZ-13 seed crystals to silicon source is 5:100;

[0107] 4) Preparation of SSZ-13 molecular sieve

[0108] The reactant gel was placed at 170°C for dynamic crystallization for 18 hours. After the crystallization was completed, it was cooled to 20-30°C, washed with deionized water until neutral, and dried at 120°C for 3 hours to obtain SSZ-13 molecular sieve.

[0109] Example 2

[0110] 1) Preparation of activated natural silica-alumina minerals

[0111] Sodium hydroxide and potassium hydroxide are used as the first alkali source, and kaolin is activated by a pseudo-solid phase activation method. The specific steps are as follows: 10g of kaolin, 4.0g of sodium hydroxide, and 11.8g of potassium hydroxide are mixed and placed in a grinder for 2min (output power 800W, speed 26000r / min), and then 2.6g of water is added, and after stirring and mixing evenly, it is placed in an extruder and kneaded twice, and then extruded to obtain wet strips with a diameter of 2.0mm, and the wet strips are activated at 250°C for 3h to obtain activated kaolin; the activated kaolin is crushed and sieved to less than 200 meshes;

[0112] The molar ratio of sodium hydroxide to the first alkali source is 0.32:1; the mass ratio of the first alkali source to kaolin is 1.58:1; the contents of active silicon and active aluminum in the activated kaolin are 96wt% and 95wt% of the silicon source and aluminum source in natural silica-alumina minerals, respectively;

[0113] 2) Preparation of the second mixture

[0114] 9.4 g of activated kaolin and 1.4 g of SSZ-13 seed crystals were mixed to obtain a first mixture; the first mixture was crushed in a crusher for 2 min (output power 800 W, speed 26000 r / min), and then ball-milled in a ball mill at a speed of 300 rpm for 60 min to obtain a second mixture; the second mixture was crushed and sieved to less than 200 mesh;

[0115] wherein the crystallinity of the SSZ-13 seed crystals in the second mixture is 57% of the SSZ-13 seed crystals in the first mixture;

[0116] 3) Preparation of reactant gel

[0117] Using sodium hydroxide and potassium hydroxide as the second alkali source, 0.62 g of sodium hydroxide and 0.08 g of potassium hydroxide were dissolved in deionized water under stirring, and then the second mixture was added, and the mixture was aged at 60° C. for 2 h, and then white carbon black was added, and the mixture was aged at 60° C. for 4 h to obtain a reactant gel;

[0118] Among them, the molar ratio of sodium hydroxide to the second alkali source is 0.92:1; in the reactant gel, the molar ratio of the alkali source, silicon source, aluminum source and water is 8.4:30:1:2000; and the mass ratio of SSZ-13 seed crystals to silicon source is 5:100.

[0119] 4) Preparation of SSZ-13 molecular sieve

[0120] The reactant gel was placed at 170°C for dynamic crystallization for 24 hours. After the crystallization was completed, it was cooled to 20-30°C, washed with deionized water until neutral, and dried at 120°C for 3 hours to obtain SSZ-13 molecular sieve.

[0121] Example 3

[0122] 1) Preparation of activated natural silica-alumina minerals

[0123] Sodium hydroxide and cesium hydroxide are used as the first alkali source, and kaolin is activated by a pseudo-solid phase activation method. The specific steps are: 10g of kaolin, 10.8g of sodium hydroxide, and 5.1g of cesium hydroxide monohydrate are mixed and crushed in a crusher for 2min (output power 800W, speed 26000r / min), and then 1.2g of water is added, and after stirring and mixing evenly, it is placed in an extruder and kneaded twice, and then extruded to obtain a wet strip with a diameter of 2.0mm, and the wet strip is activated at 250℃ for 3h to obtain activated kaolin; the activated kaolin is crushed and sieved to less than 200 meshes;

[0124] The molar ratio of sodium hydroxide to the first alkali source is 0.89:1; the mass ratio of the first alkali source to kaolin is 1.59:1; the contents of active silicon and active aluminum in the activated kaolin are 93wt% and 95wt% of the silicon source and aluminum source in natural silica-aluminum minerals, respectively;

[0125] 2) Preparation of the second mixture

[0126] 10.5 g of activated kaolin and 1.6 g of SSZ-13 seed crystals were mixed to obtain a first mixture; the first mixture was crushed in a pulverizer for 2 min (output power 800 W, speed 26000 r / min), and then ball-milled in a ball mill at a speed of 300 rpm for 60 min to obtain a second mixture; the second mixture was crushed and sieved to less than 200 mesh;

[0127] wherein the crystallinity of the SSZ-13 seed crystals in the second mixture is 61% of the SSZ-13 seed crystals in the first mixture;

[0128] 3) Preparation of reactant gel

[0129] Using sodium hydroxide and cesium hydroxide monohydrate as the second alkali source, 0.41 g of sodium hydroxide and 0.39 g of cesium hydroxide monohydrate were dissolved in deionized water under stirring, and then the second mixture was added, aged at 60° C. for 2 h, and then white carbon black was added, and the reaction was further aged at 60° C. for 4 h to obtain a reactant gel;

[0130] The molar ratio of sodium hydroxide to the second alkali source is 0.80:1; the molar ratio of the alkali source, silicon source, aluminum source and water in the reactant gel is 7:30:1:1800; the mass ratio of the SSZ-13 seed crystal to the silicon source is 5:100;

[0131] 4) Preparation of SSZ-13 molecular sieve

[0132] The reactant gel was placed at 170°C for dynamic crystallization for 18 hours. After the crystallization was completed, it was cooled by 20-30°C, washed with deionized water until neutral, and dried at 120°C for 3 hours to obtain SSZ-13 molecular sieve.

[0133] Example 4

[0134] 1) Preparation of activated natural silica-alumina minerals

[0135] Sodium hydroxide and potassium hydroxide are used as the first alkali source, and kaolin is activated by a pseudo-solid phase activation method. The specific steps are as follows: 10g of kaolin, 4.0g of sodium hydroxide, and 11.8g of potassium hydroxide are mixed and crushed in a crusher for 2min (output power 800W, speed 26000r / min), and then 2.6g of water is added, and after stirring and mixing evenly, it is placed in an extruder and kneaded twice, and then extruded to obtain a wet strip with a diameter of 2.0mm, and the wet strip is activated at 250°C for 3h to obtain activated kaolin; the activated kaolin is crushed and sieved to less than 200 mesh;

[0136] The molar ratio of sodium hydroxide to the first alkali source is 0.32:1; the mass ratio of the first alkali source to kaolin is 1.58:1; the contents of active silicon and active aluminum in the activated kaolin are 93wt% and 96wt% of the silicon source and aluminum source in natural silica-alumina minerals, respectively;

[0137] 2) Preparation of the second mixture

[0138] 28.2 g of activated kaolin and 4.2 g of SSZ-13 seed crystals were mixed to obtain a first mixture; the first mixture was crushed in a crusher for 2 min (output power 800 W, speed 26000 r / min), and then 10% of water relative to the total mass of the solid was added, and after kneading evenly, it was placed in a twin-screw extruder for mixing and extrusion to obtain wet strips with a diameter of 2 mm, and the wet strips were placed at 60° C. and dried for 4 h, and then crushed again and sieved to less than 200 mesh;

[0139] wherein the crystallinity of the SSZ-13 seed crystals in the second mixture is 45% of the SSZ-13 seed crystals in the first mixture;

[0140] 3) Preparation of reactant gel

[0141] Using sodium hydroxide and potassium hydroxide as the second alkali source, 0.62 g of sodium hydroxide and 0.08 g of potassium hydroxide were dissolved in deionized water under stirring, and then the second mixture was added, and aged at 60° C. for 2 h, and then white carbon black was added, and the temperature was further aged at 60° C. for 4 h to obtain a reactant gel;

[0142] The molar ratio of sodium hydroxide to the second alkali source is 0.92:1; the molar ratio of the alkali source, silicon source, aluminum source and water in the reactant gel is 8.4:30:1:2000; the mass ratio of the SSZ-13 seed crystal to the silicon source is 5:100;

[0143] 4) Preparation of SSZ-13 molecular sieve

[0144] The reactant gel was placed at 170°C for dynamic crystallization for 18 hours. After the crystallization was completed, it was cooled by 20-30°C, washed with deionized water until neutral, and dried at 120°C for 3 hours to obtain SSZ-13 molecular sieve.

[0145] Example 5

[0146] 1) Preparation of activated natural silica-alumina minerals

[0147] Sodium hydroxide and cesium hydroxide are used as the first alkali source, and kaolin is activated by a pseudo-solid phase activation method. The specific steps are: 10.0g of kaolin, 10.8g of sodium hydroxide, and 5.1g of cesium hydroxide monohydrate are mixed and crushed in a crusher for 2min (output power 800W, speed 26000r / min), and then 2.6g of water is added, and after stirring and mixing evenly, it is placed in an extruder and kneaded twice, and then extruded to obtain a wet strip with a diameter of 2.0mm, and the wet strip is activated at 250℃ for 3h to obtain activated kaolin; the activated kaolin is crushed and sieved to less than 200 mesh;

[0148] The molar ratio of sodium hydroxide to the first alkali source is 0.89:1; the mass ratio of the first alkali source to kaolin is 1.59:1; the contents of active silicon and active aluminum in the activated kaolin are 95wt% and 96wt% of the silicon source and aluminum source in natural silica-alumina minerals, respectively;

[0149] 2) Preparation of the second mixture

[0150] 10.5 g of activated kaolin and 1.6 g of SSZ-13 seed crystals were mixed to obtain a first mixture; the first mixture was crushed in a crusher for 2 min (output power 800 W, speed 26000 r / min), and then ball-milled at a speed of 300 rpm for 60 min to obtain a second mixture; the second mixture was crushed and sieved to less than 200 mesh;

[0151] wherein the crystallinity of the SSZ-13 seed crystals in the second mixture is 58% of the SSZ-13 seed crystals in the first mixture;

[0152] 3) Preparation of reactant gel

[0153] Using sodium hydroxide and cesium hydroxide monohydrate as the second alkali source, 0.41 g of sodium hydroxide and 0.39 g of cesium hydroxide monohydrate were dissolved in deionized water under stirring, and then the second mixture was added, aged at 60° C. for 2 h, and then white carbon black was added, and the reaction was further aged at 60° C. for 4 h to obtain a reactant gel;

[0154] The molar ratio of sodium hydroxide to the second alkali source is 0.80:1; the molar ratio of the alkali source, silicon source, aluminum source and water in the reactant gel is 7:20:1:1800; the mass ratio of the SSZ-13 seed crystal to the silicon source is 5:100;

[0155] 4) Preparation of SSZ-13 molecular sieve

[0156] The reactant gel was placed at 160°C for dynamic crystallization for 30 hours. After the crystallization was completed, it was cooled by 20-30°C, washed with deionized water until neutral, and dried at 120°C for 3 hours to obtain SSZ-13 molecular sieve.

[0157] Example 6

[0158] 1) Preparation of activated natural silica-alumina minerals

[0159] Sodium hydroxide and potassium hydroxide are used as the first alkali source, and kaolin is activated by a pseudo-solid phase activation method. The specific steps are as follows: 10.0g of kaolin, 4.0g of sodium hydroxide, and 11.8g of potassium hydroxide are mixed and crushed in a crusher for 2min (output power 800W, speed 26000r / min), and then 2.6g of water is added, and after stirring and mixing evenly, it is placed in an extruder and kneaded twice, and then extruded to obtain a wet strip with a diameter of 2.0mm, and the wet strip is activated at 250℃ for 3h to obtain activated kaolin; the activated kaolin is crushed and sieved to less than 200 mesh;

[0160] The molar ratio of sodium hydroxide to the first alkali source is 0.32:1; the mass ratio of the first alkali source to kaolin is 1.58:1; the contents of active silicon and active aluminum in the activated kaolin are 95wt% and 94wt% of the silicon source and aluminum source in natural silica-aluminum minerals, respectively;

[0161] 2) Preparation of the second mixture

[0162] 28.2 g of activated kaolin and 4.2 g of SSZ-13 seed crystals were mixed to obtain a first mixture; the first mixture was crushed in a crusher for 2 min (output power 800 W, speed 26000 r / min), and then 10% of water relative to the total mass of the solid was added, and after kneading evenly, it was placed in a twin-screw extruder for mixing and extrusion to obtain wet strips with a diameter of 2 mm, and the wet strips were placed at 60° C. and dried for 4 h, and then crushed again and sieved to less than 200 mesh;

[0163] wherein the crystallinity of the SSZ-13 seed crystals in the second mixture is 48% of the SSZ-13 seed crystals in the first mixture;

[0164] 3) Preparation of reactant gel

[0165] Using sodium hydroxide and potassium hydroxide as the second alkali source, 0.62 g of sodium hydroxide and 0.08 g of potassium hydroxide were dissolved in deionized water under stirring, and then added to the second mixture and aged at 60° C. for 2 h. TMAdaOH was added to the aged second mixture, and after stirring for 0.5 h, silica gel was added, and then further aged at 60° C. for 4 h to obtain a reactant gel;

[0166] The molar ratio of sodium hydroxide to the second alkali source is 0.92:1; the molar ratio of the alkali source, silicon source, aluminum source and water in the reactant gel is 8.4:30:1:2000; the mass ratio of SSZ-13 seed crystal to silicon source is 5:100; the molar ratio of TMAdaOH to silicon source is 0.005:1;

[0167] 4) Preparation of SSZ-13 molecular sieve

[0168] The reactant gel was placed at 170°C for dynamic crystallization for 12 hours. After the crystallization was completed, it was cooled by 20-30°C, washed with deionized water until neutral, and dried at 120°C for 3 hours to obtain SSZ-13 molecular sieve.

[0169] Example 7

[0170] 1) Preparation of activated natural silica-alumina minerals

[0171] Sodium hydroxide and potassium hydroxide are used as the first alkali source, and kaolin is activated by a pseudo-solid phase activation method. The specific steps are as follows: 10.0g of kaolin, 4.0g of sodium hydroxide, and 11.8g of potassium hydroxide are mixed and crushed in a crusher for 2min (output power 800W, speed 26000r / min), and then 2.6g of water is added, and after stirring and mixing evenly, it is placed in an extruder and kneaded twice, and then extruded to obtain a wet strip with a diameter of 2.0mm, and the wet strip is activated at 250℃ for 3h to obtain activated kaolin; the activated kaolin is crushed and sieved to less than 200 mesh;

[0172] The molar ratio of sodium hydroxide to the first alkali source is 0.32:1; the mass ratio of the first alkali source to kaolin is 1.58:1; the contents of active silicon and active aluminum in the activated kaolin are 93wt% and 96wt% of the silicon source and aluminum source in natural silica-alumina minerals, respectively;

[0173] 2) Preparation of the second mixture

[0174] 9.9 g of activated kaolin and 5.1 g of SSZ-13 seed crystals were mixed to obtain a first mixture; the first mixture was crushed in a crusher for 2 min (output power 800 W, speed 26000 r / min) to obtain a second mixture, and the second mixture was sieved to less than 200 mesh;

[0175] wherein the crystallinity of the SSZ-13 seed crystals in the second mixture is 72% of the SSZ-13 seed crystals in the first mixture;

[0176] 3) Preparation of reactant gel

[0177] Using sodium hydroxide and potassium hydroxide as the second alkali source, 1.06 g of sodium hydroxide and 0.43 g of potassium hydroxide were dissolved in deionized water under stirring, and then added to the second mixture and aged at 60° C. for 2 h. TMAdaOH was added to the aged second mixture, and white carbon black was added after stirring for 0.5 h, and then aged at 60° C. for 4 h to obtain a reactant gel;

[0178] The molar ratio of sodium hydroxide to the second alkali source is 0.77:1; the molar ratio of the alkali source, silicon source, aluminum source and water in the reactant gel is 13.5:100:1:1900; the mass ratio of SSZ-13 seed crystal to silicon source is 5:100; the molar ratio of TMAdaOH to silicon source is 0.001:1;

[0179] 4) Preparation of SSZ-13 molecular sieve

[0180] The reactant gel was placed at 170°C for dynamic crystallization for 18 hours. After the crystallization was completed, it was cooled by 20-30°C, washed with deionized water until neutral, and dried at 120°C for 3 hours to obtain SSZ-13 molecular sieve.

[0181] Example 8

[0182] Sodium hydroxide and potassium hydroxide are used as the first alkali source, and the pseudo-solid phase activation method is used to activate the rector soil. The specific steps are as follows: 10.0g of rector soil, 4.0g of sodium hydroxide and 11.8g of potassium hydroxide are mixed and crushed in a crusher for 2min (output power 800W, speed 26000r / min), and then 2.6g of water is added, and after stirring and mixing evenly, it is placed in an extruder and kneaded twice, and then extruded to obtain a wet strip with a diameter of 2.0mm, and the wet strip is activated at 250℃ for 3h to obtain activated rector soil; the activated rector soil is crushed and sieved to less than 200 meshes;

[0183] The molar ratio of sodium hydroxide to the first alkali source is 0.32:1; the mass ratio of the first alkali source to the rectorite is 1.58:1; the contents of active silicon and active aluminum in the activated rectorite are 95wt% and 94wt% of the silicon source and aluminum source in the natural silica-alumina mineral, respectively;

[0184] 2) Preparation of the second mixture

[0185] 10.2 g of activated rectorite and 0.29 g of SSZ-13 seed crystals were mixed to obtain a first mixture; the first mixture was crushed in a crusher for 2 min (output power 800 W, speed 26000 r / min), and then ball-milled at a speed of 300 rpm for 60 min to obtain a second mixture; the second mixture was crushed and sieved to less than 200 mesh;

[0186] wherein the crystallinity of the SSZ-13 seed crystals in the second mixture is 67% of the SSZ-13 seed crystals in the first mixture;

[0187] 3) Preparation of reactant gel

[0188] Using sodium hydroxide and potassium hydroxide as the second alkali source, 0.42 g of sodium hydroxide and 0.20 g of potassium hydroxide were dissolved in deionized water under stirring, and then the second mixture was added, and the mixture was aged at 60° C. for 2 h, and then white carbon black was added, and the mixture was aged at 60° C. for 4 h to obtain a reactant gel;

[0189] Among them, the molar ratio of sodium hydroxide to the second alkali source is 0.74:1; in the reactant gel, the molar ratio of the alkali source, silicon source, aluminum source and water is 8.4:30:1:2000; and the mass ratio of SSZ-13 seed crystals to silicon source is 0.1:100.

[0190] 4) Preparation of SSZ-13 molecular sieve

[0191] The reactant gel was placed at 170°C for dynamic crystallization for 24 hours. After the crystallization was completed, it was cooled by 20-30°C, washed with deionized water until neutral, and dried at 120°C for 3 hours to obtain SSZ-13 molecular sieve.

[0192] Example 9

[0193] 1) Preparation of activated natural silica-alumina minerals

[0194] Sodium hydroxide and potassium hydroxide are used as the first alkali source, and kaolin is activated by a pseudo-solid phase activation method. The specific steps are as follows: 10.0g of kaolin, 4.0g of sodium hydroxide and 11.8g of potassium hydroxide are mixed and crushed in a grinder for 2 minutes, and then 60g of water is added, and after stirring and mixing evenly, the mixture is placed in an extruder and kneaded twice, and then extruded to obtain wet strips with a diameter of 2.0mm, and the wet strips are activated at 250°C for 3h to obtain activated kaolin; the activated kaolin is crushed and sieved to less than 120 meshes;

[0195] The molar ratio of sodium hydroxide to the first alkali source is 0.32:1; the mass ratio of the first alkali source to kaolin is 1.58:1; the contents of active silicon and active aluminum in the activated kaolin are 93wt% and 95wt% of the silicon source and aluminum source in natural silica-alumina minerals, respectively;

[0196] 2) Preparation of the second mixture

[0197] 9.4 g of activated kaolin and 1.4 g of SSZ-13 seed crystals were mixed to obtain a first mixture; the first mixture was crushed in a crusher for 2 min, and then ball-milled at a speed of 300 rpm for 60 min to obtain a second mixture; the second mixture was crushed and sieved to less than 200 mesh;

[0198] wherein the crystallinity of the SSZ-13 seed crystals in the second mixture is 67% of the SSZ-13 seed crystals in the first mixture;

[0199] 3) Preparation of reactant gel

[0200] Using sodium hydroxide and potassium hydroxide as the second alkali source, 0.62 g of sodium hydroxide and 0.08 g of potassium hydroxide were dissolved in deionized water under stirring, and then the second mixture was added, and the mixture was aged at 60° C. for 2 h, and then white carbon black was added, and the mixture was aged at 60° C. for 4 h to obtain a reactant gel;

[0201] Among them, the molar ratio of sodium hydroxide to the second alkali source is 0.92:1; in the reactant gel, the molar ratio of the alkali source, silicon source, aluminum source and water is 8.4:30:1:2000; and the mass ratio of SSZ-13 seed crystals to silicon source is 5:100.

[0202] 4) Preparation of SSZ-13 molecular sieve

[0203] The reactant gel was placed at 170°C for dynamic crystallization for 24 hours. After the crystallization was completed, it was cooled by 20-30°C, washed with deionized water until neutral, and dried at 120°C for 3 hours to obtain SSZ-13 molecular sieve.

[0204] Example 10

[0205] 1) Preparation of activated natural silica-alumina minerals

[0206] Sodium hydroxide and potassium hydroxide are used as the first alkali source, and kaolin is activated by a pseudo-solid phase activation method. The specific steps are: 10.0g of kaolin, 6.0g of sodium hydroxide, and 9.9g of potassium hydroxide are mixed and crushed in a grinder for 2 minutes, and then 2.6g of water is added, and after stirring and mixing evenly, it is placed in an extruder and kneaded twice, and then extruded to obtain wet strips with a diameter of 2.0mm, and the wet strips are activated at 250°C for 3h to obtain activated kaolin; the activated kaolin is crushed and sieved to less than 200 meshes;

[0207] The molar ratio of sodium hydroxide to the first alkali source is 0.46:1; the mass ratio of the first alkali source to kaolin is 1.59:1; the contents of active silicon and active aluminum in the activated kaolin are 95wt% and 95wt% of the silicon source and aluminum source in natural silica-alumina minerals, respectively;

[0208] 2) Preparation of the second mixture

[0209] 9.6 g of activated kaolin and 1.4 g of SSZ-13 seed crystals were mixed to obtain a first mixture; the first mixture was crushed in a crusher for 2 min (output power 800 W, speed 26000 r / min), and then ball-milled at a speed of 300 rpm for 60 min to obtain a second mixture; the second mixture was crushed and sieved to less than 200 mesh;

[0210] wherein the crystallinity of the SSZ-13 seed crystals in the second mixture is 67% of the SSZ-13 seed crystals in the first mixture;

[0211] 3) Preparation of reactant gel

[0212] Using sodium hydroxide and potassium hydroxide as the second alkali source, 0.62 g of sodium hydroxide and 0.05 g of potassium hydroxide were dissolved in deionized water under stirring, and then the second mixture was added, and the mixture was aged at 60° C. for 2 h, and then white carbon black was added, and the mixture was aged at 60° C. for 4 h to obtain a reactant gel;

[0213] Among them, the molar ratio of sodium hydroxide to the second alkali source is 0.92:1; in the reactant gel, the molar ratio of the alkali source, silicon source, aluminum source and water is 8.4:30:1:2000; and the mass ratio of SSZ-13 seed crystals to silicon source is 5:100.

[0214] 4) Preparation of SSZ-13 molecular sieve

[0215] The reactant gel was placed at 170°C for dynamic crystallization for 24 hours. After the crystallization was completed, it was cooled by 20-30°C, washed with deionized water until neutral, and dried at 120°C for 3 hours to obtain SSZ-13 molecular sieve.

[0216] Embodiment 11

[0217] 1) Preparation of activated natural silica-alumina minerals

[0218] Sodium hydroxide and potassium hydroxide are used as the first alkali source, and kaolin is activated by a pseudo-solid phase activation method. The specific steps are as follows: 10.0g of kaolin, 6.7g of sodium hydroxide, and 4.9g of potassium hydroxide are mixed and crushed in a crusher for 2min (output power 800W, speed 26000r / min), and then 2.6g of water is added, and after stirring and mixing evenly, it is placed in an extruder and kneaded twice, and then extruded to obtain a wet strip with a diameter of 2.0mm, and the wet strip is activated at 250°C for 3h to obtain activated kaolin; the activated kaolin is crushed and sieved to less than 200 mesh;

[0219] The molar ratio of sodium hydroxide to the first alkali source is 0.65:1; the mass ratio of the first alkali source to kaolin is 1.16:1; the contents of active silicon and active aluminum in the activated kaolin are 96wt% and 94wt% of the silicon source and aluminum source in natural silica-alumina minerals, respectively;

[0220] 2) Preparation of the second mixture

[0221] 7.95 g of activated kaolin and 1.44 g of SSZ-13 seed crystals were mixed to obtain a first mixture; the first mixture was crushed in a crusher for 2 min, and then ball-milled at a speed of 300 rpm for 60 min to obtain a second mixture; the second mixture was crushed and sieved to less than 200 mesh;

[0222] wherein the crystallinity of the SSZ-13 seed crystals in the second mixture is 66% of the SSZ-13 seed crystals in the first mixture;

[0223] 3) Preparation of reactant gel

[0224] Using sodium hydroxide and potassium hydroxide as the second alkali source, 0.52 g of sodium hydroxide and 0.27 g of potassium hydroxide were dissolved in deionized water under stirring, and then the second mixture was added, aged at 60° C. for 2 h, and then white carbon black was added, and the reaction was further aged at 60° C. for 4 h to obtain a reactant gel;

[0225] Among them, the molar ratio of sodium hydroxide to the second alkali source is 0.73:1; in the reactant gel, the molar ratio of the alkali source, silicon source, aluminum source and water is 8.4:30:1:2000; and the mass ratio of SSZ-13 seed crystals to silicon source is 5:100.

[0226] 4) Preparation of SSZ-13 molecular sieve

[0227] The reactant gel was placed at 170°C for dynamic crystallization for 24 hours. After the crystallization was completed, it was cooled by 20-30°C, washed with deionized water until neutral, and dried at 120°C for 3 hours to obtain SSZ-13 molecular sieve.

[0228] Example 12

[0229] 1) Preparation of activated natural silica-alumina minerals

[0230] Sodium hydroxide and potassium hydroxide are used as the first alkali source, and kaolin is activated by a pseudo-solid phase activation method. The specific steps are as follows: 10.0g of kaolin, 13.3g of sodium hydroxide, and 9.35g of potassium hydroxide are mixed and crushed in a crusher for 2min (output power 800W, speed 26000r / min), and then 2.6g of water is added, and after stirring and mixing evenly, it is placed in an extruder and kneaded twice, and then extruded to obtain a wet strip with a diameter of 2.0mm, and the wet strip is activated at 250℃ for 3h to obtain activated kaolin; the activated kaolin is crushed and sieved to less than 200 mesh;

[0231] The molar ratio of sodium hydroxide to the first alkali source is 0.66:1; the mass ratio of the first alkali source to kaolin is 2.27:1; the contents of active silicon and active aluminum in the activated kaolin are 97wt% and 95wt% of the silicon source and aluminum source in natural silica-alumina minerals, respectively;

[0232] 2) Preparation of the second mixture

[0233] 12.2 g of activated kaolin and 1.44 g of SSZ-13 seed crystals were mixed to obtain a first mixture; the first mixture was crushed in a crusher for 2 min, and then ball-milled at a speed of 300 rpm for 60 min to obtain a second mixture; the second mixture was crushed and sieved to less than 200 mesh;

[0234] wherein the crystallinity of the SSZ-13 seed crystals in the second mixture is 68% of the SSZ-13 seed crystals in the first mixture;

[0235] 3) Preparation of reactant gel

[0236] Using sodium hydroxide and potassium hydroxide as the second alkali source, 0.27 g of sodium hydroxide and 0.0068 g of potassium hydroxide were dissolved in deionized water under stirring, and then the second mixture was added, and the mixture was aged at 60° C. for 2 h, and then white carbon black was added, and the mixture was aged at 60° C. for 4 h to obtain a reactant gel;

[0237] Among them, the molar ratio of sodium hydroxide to the second alkali source is 0.82:1; in the reactant gel, the molar ratio of the alkali source, silicon source, aluminum source and water is 8.4:30:1:2000; and the mass ratio of SSZ-13 seed crystals to silicon source is 5:100.

[0238] 4) Preparation of SSZ-13 molecular sieve

[0239] The reactant gel was placed at 170°C for dynamic crystallization for 24 hours. After the crystallization was completed, it was cooled by 20-30°C, washed with deionized water until neutral, and dried at 120°C for 3 hours to obtain SSZ-13 molecular sieve.

[0240] Embodiment 13

[0241] 1) Preparation of activated natural silica-alumina minerals

[0242] Sodium hydroxide and potassium hydroxide are used as the first alkali source, and kaolin is activated by a pseudo-solid phase activation method. The specific steps are: 10.0g of kaolin, 4.0g of sodium hydroxide, and 11.8g of potassium hydroxide are mixed and crushed in a crusher for 2min (output power 800W, speed 26000r / min), and then 2.6g of water is added, and after stirring and mixing evenly, it is placed in an extruder and kneaded twice, and then extruded to obtain wet strips with a diameter of 2.0mm, and the wet strips are activated at 250℃ for 3h to obtain activated kaolin; the activated kaolin is crushed and sieved to less than 120 mesh;

[0243] The molar ratio of sodium hydroxide to the first alkali source is 0.32:1; the mass ratio of the first alkali source to kaolin is 1.58:1; the contents of active silicon and active aluminum in the activated kaolin are 93wt% and 95wt% of the silicon source and aluminum source in natural silica-alumina minerals, respectively;

[0244] 2) Preparation of the second mixture

[0245] 9.4 g of activated kaolin and 1.4 g of SSZ-13 seed crystals were mixed to obtain a first mixture; the first mixture was crushed in a crusher for 2 min, and then ball-milled at a speed of 300 rpm for 60 min to obtain a second mixture; the second mixture was crushed and sieved to less than 100 mesh;

[0246] wherein the crystallinity of the SSZ-13 seed crystals in the second mixture is 67% of the SSZ-13 seed crystals in the first mixture;

[0247] 3) Preparation of reactant gel

[0248] Using sodium hydroxide and potassium hydroxide as the second alkali source, 0.62 g of sodium hydroxide and 0.08 g of potassium hydroxide were dissolved in deionized water under stirring, and then the second mixture was added, and the mixture was aged at 60° C. for 2 h, and then white carbon black was added, and the mixture was aged at 60° C. for 4 h to obtain a reactant gel;

[0249] Among them, the molar ratio of sodium hydroxide to the second alkali source is 0.92:1; in the reactant gel, the molar ratio of the alkali source, silicon source, aluminum source and water is 8.4:30:1:2000; and the mass ratio of SSZ-13 seed crystals to silicon source is 5:100.

[0250] 4) Preparation of SSZ-13 molecular sieve

[0251] The reactant gel was placed at 170°C for dynamic crystallization for 24 hours. After the crystallization was completed, it was cooled by 20-30°C, washed with deionized water until neutral, and dried at 120°C for 3 hours to obtain SSZ-13 molecular sieve.

[0252] Embodiment 14

[0253] 1) Preparation of activated natural silica-alumina minerals

[0254] Sodium hydroxide and potassium hydroxide are used as the first alkali source, and kaolin is activated by a pseudo-solid phase activation method. The specific steps are as follows: 10g of kaolin, 4.0g of sodium hydroxide, and 11.8g of potassium hydroxide are mixed and crushed in a crusher for 2min (output power 800W, speed 26000r / min), and then 2.6g of water is added, and after stirring and mixing evenly, it is placed in an extruder and kneaded twice, and then extruded to obtain a wet strip with a diameter of 2.0mm, and the wet strip is activated at 250°C for 3h to obtain activated kaolin; the activated kaolin is crushed and sieved to less than 200 mesh;

[0255] The molar ratio of sodium hydroxide to the first alkali source is 0.32:1; the mass ratio of the first alkali source to kaolin is 1.58:1; the contents of active silicon and active aluminum in the activated kaolin are 95wt% and 94wt% of the silicon source and aluminum source in natural silica-aluminum minerals, respectively;

[0256] 2) Preparation of the second mixture

[0257] 28.2 g of activated kaolin and 4.2 g of SSZ-13 seed crystals were mixed to obtain a first mixture; the first mixture was crushed in a crusher for 2 min (output power 800 W, rotation speed 26000 r / min), and then 5% of water relative to the total mass of the solid was added, and after kneading evenly, it was placed in a twin-screw extruder for mixing and extrusion to obtain wet strips with a diameter of 2 mm, and the wet strips were placed at 60° C. and dried for 4 h, and then crushed again and sieved to less than 200 mesh;

[0258] wherein the crystallinity of the SSZ-13 seed crystals in the second mixture is 58% of the SSZ-13 seed crystals in the first mixture;

[0259] 3) Preparation of reactant gel

[0260] Using sodium hydroxide and potassium hydroxide as the second alkali source, 0.62 g of sodium hydroxide and 0.08 g of potassium hydroxide were dissolved in deionized water under stirring, and then added to the second mixture and aged at 60° C. for 2 h. 0.20 g of TMAdaOH was added to the aged second mixture, and after stirring for 0.5 h, silica gel was added, and then further aged at 60° C. for 4 h to obtain a reactant gel;

[0261] The molar ratio of sodium hydroxide to the second alkali source is 0.92:1; the molar ratio of the alkali source, silicon source, aluminum source and water in the reactant gel is 8.4:30:1:2000; the mass ratio of SSZ-13 seed crystal to silicon source is 5:100; the molar ratio of TMAdaOH to silicon source is 0.005:1;

[0262] 4) Preparation of SSZ-13 molecular sieve

[0263] The reactant gel was placed at 170°C for dynamic crystallization for 12 hours. After the crystallization was completed, it was cooled by 20-30°C, washed with deionized water until neutral, and dried at 120°C for 3 hours to obtain SSZ-13 molecular sieve.

[0264] Comparative Example 1

[0265] 1) Preparation of activated natural silica-alumina minerals

[0266] Sodium hydroxide is used as the first alkali source, and kaolin is activated by a sub-molten salt activation method. The specific steps are: 13.9g of sodium hydroxide and 60g of deionized water are mixed and added into a polytetrafluoroethylene activation kettle, 10g of kaolin is added under stirring, and the activation kettle is placed in an oven at 250°C for activation for 3h to obtain activated kaolin; the activated kaolin is crushed and sieved to less than 200 mesh;

[0267] The mass ratio of the first alkali source to kaolin is 1.39:1; the contents of active silicon and active aluminum in the activated kaolin are 91wt% and 92wt% of the silicon source and aluminum source in natural silica-alumina minerals, respectively;

[0268] 2) Preparation of the second mixture

[0269] 9.1 g of activated kaolin and 1.1 g of SSZ-13 seed crystals were mixed to obtain a first mixture; the first mixture was crushed in a crusher for 2 min (output power 800 W, speed 26000 r / min), and then ball-milled in a ball mill at a speed of 300 rpm for 60 min to obtain a second mixture; the second mixture was crushed and sieved to less than 200 mesh;

[0270] wherein the crystallinity of the SSZ-13 seed crystals in the second mixture is 67% of the SSZ-13 seed crystals in the first mixture;

[0271] 3) Preparation of reactant gel

[0272] Using sodium hydroxide and potassium hydroxide as the second alkali source, 0.32 g of sodium hydroxide and 0.15 g of potassium hydroxide were dissolved in deionized water under stirring, and then the second mixture was added, aged at 60° C. for 2 h, and then white carbon black was added, and the reaction was further aged at 60° C. for 4 h to obtain a reactant gel;

[0273] The molar ratio of sodium hydroxide to the second alkali source is 0.75:1; the molar ratio of the alkali source, silicon source, aluminum source and water in the reactant gel is 7:20:1:1800; the mass ratio of SSZ-13 seed crystal to silicon source is 5:100;

[0274] 4) Preparation of molecular sieves

[0275] The reactant gel was placed at 170°C for dynamic crystallization for 18 hours. After the crystallization was completed, it was cooled by 20-30°C, washed with deionized water until neutral, and dried at 120°C for 3 hours to obtain a molecular sieve.

[0276] Comparative Example 2

[0277] 1) Preparation of activated natural silica-alumina minerals

[0278] Sodium hydroxide and potassium hydroxide are used as the first alkali source, and kaolin is activated by a sub-molten salt activation method. The specific steps are: 8.0g of sodium hydroxide, 5.9g of potassium hydroxide, and 60g of deionized water are mixed and added into a polytetrafluoroethylene activation kettle, 10g of kaolin is added under stirring, and the activation kettle is placed in an oven at 250°C for activation for 3h to obtain activated kaolin; the activated kaolin is crushed and sieved to less than 200 meshes;

[0279] The molar ratio of sodium hydroxide to the first alkali source is 0.67:1; the mass ratio of the first alkali source to kaolin is 1.39:1; the contents of active silicon and active aluminum in the activated kaolin are 93wt% and 95wt% of the silicon source and aluminum source in natural silica-alumina minerals, respectively;

[0280] 2) Preparation of the second mixture

[0281] 9.8 g of activated kaolin and 1.1 g of SSZ-13 seed crystals were mixed to obtain a first mixture; the first mixture was crushed in a crusher for 2 min (output power 800 W, speed 26000 r / min), and then ball-milled in a ball mill at a speed of 300 rpm for 60 min to obtain a second mixture; the second mixture was crushed and sieved to less than 200 mesh;

[0282] 3) Preparation of reactant gel

[0283] Using sodium hydroxide as the second alkali source, 0.51 g of sodium hydroxide was dissolved in deionized water under stirring, and then the second mixture was added, and the mixture was aged at 60° C. for 2 h, and then white carbon black was added, and the mixture was aged at 60° C. for 4 h to obtain a reactant gel;

[0284] In the reactant gel, the molar ratio of alkali source, silicon source, aluminum source and water is 7:20:1:1800; the mass ratio of SSZ-13 seed crystal to silicon source is 5:100;

[0285] 4) Preparation of molecular sieves

[0286] The reactant gel was placed at 170°C for dynamic crystallization for 18 hours. After the crystallization was completed, it was cooled by 20-30°C, washed with deionized water until neutral, and dried at 120°C for 3 hours to obtain a molecular sieve.

[0287] Comparative Example 3

[0288] 1) Preparation of activated natural silica-alumina minerals

[0289] Sodium hydroxide and potassium hydroxide are used as the first alkali source, and kaolin is activated by a sub-molten salt activation method. The specific steps are: 8.0g of sodium hydroxide, 5.9g of potassium hydroxide, and 60g of deionized water are mixed and added into a polytetrafluoroethylene activation kettle, 10g of kaolin is added under stirring, and the activation kettle is placed in an oven at 250°C for activation for 3h to obtain activated kaolin; the activated kaolin is crushed and sieved to less than 200 meshes;

[0290] The molar ratio of sodium hydroxide to the first alkali source is 0.66:1; the mass ratio of the first alkali source to kaolin is 1.39:1; the contents of active silicon and active aluminum in the activated kaolin are 93wt% and 95wt% of the silicon source and aluminum source in natural silica-alumina minerals, respectively;

[0291] 2) Preparation of the first mixture

[0292] Mixing 9.8 g of activated kaolin and 1.1 g of SSZ-13 seed crystals to obtain a first mixture;

[0293] 3) Preparation of reactant gel

[0294] Using sodium hydroxide and potassium hydroxide as the second alkali source, 0.38 g of sodium hydroxide and 0.18 g of potassium hydroxide were dissolved in deionized water under stirring, and then the first mixture was added, and the mixture was aged at 60° C. for 2 h, and then white carbon black was added, and the mixture was aged at 60° C. for 4 h to obtain a reactant gel;

[0295] The molar ratio of sodium hydroxide to the second alkali source is 0.75:1; the total molar ratio of the alkali source, silicon source, aluminum source and water in the reactant gel is 7:20:1:1800 (in the form of oxides); the mass ratio of the SSZ-13 seed crystal to the silicon source is 5:100;

[0296] 4) Preparation of SSZ-13 molecular sieve

[0297] The reactant gel was placed at 170°C for dynamic crystallization for 18 hours. After the crystallization was completed, it was cooled by 20-30°C, washed with deionized water until neutral, and dried at 120°C for 3 hours to obtain a molecular sieve.

[0298] Comparative Example 4

[0299] 1) Preparation of the second mixture

[0300] 9.8 g of unactivated kaolin (with active silicon and active aluminum contents of 5 wt% and 9 wt% respectively), 8.0 g of sodium hydroxide, 5.9 g of potassium hydroxide and 1.1 g of SSZ-13 seed crystals were mixed to obtain a first mixture; the first mixture was crushed in a crusher for 2 min (output power 800 W, rotation speed 26000 r / min), and then ball-milled at a rotation speed of 300 rpm for 60 min to obtain a second mixture; the second mixture was crushed and sieved to less than 200 mesh;

[0301] wherein the relative crystallinity of the SSZ-13 seed crystals in the second mixture is 67% of the SSZ-13 seed crystals in the first mixture;

[0302] 2) Preparation of reactant gel

[0303] Using sodium hydroxide and potassium hydroxide as the second alkali source, 0.38 g of sodium hydroxide and 0.18 g of potassium hydroxide were dissolved in deionized water under stirring, and then the second mixture was added, and the mixture was aged at 60° C. for 2 h, and then white carbon black was added, and the mixture was aged at 60° C. for 4 h to obtain a reactant gel;

[0304] The molar ratio of sodium hydroxide to the second alkali source is 0.75:1; the molar ratio of the alkali source, silicon source, aluminum source and water in the reactant gel is 7:20:1:1800; the mass ratio of the SSZ-13 seed crystal to the silicon source is 5:100;

[0305] 3) Preparation of molecular sieves

[0306] The reactant gel was placed at 170°C for dynamic crystallization for 18 hours. After the crystallization was completed, it was cooled to 20-30°C, washed with deionized water until neutral, and dried at 120°C for 3 hours to obtain a molecular sieve.

[0307] Comparative Example 5

[0308] 1) Preparation of activated natural silica-alumina minerals

[0309] Sodium hydroxide and potassium hydroxide are used as the first alkali source, and kaolin is activated by a sub-molten salt activation method. The specific steps are: 8.0g of sodium hydroxide, 5.9g of potassium hydroxide, and 60g of deionized water are mixed and added into a polytetrafluoroethylene activation kettle, 10g of kaolin is added under stirring, and the activation kettle is placed in an oven at 250°C for activation for 3h to obtain activated kaolin; the activated kaolin is crushed and sieved to less than 200 meshes;

[0310] The molar ratio of sodium hydroxide to the first alkali source is 0.66:1; the mass ratio of the first alkali source to kaolin is 1.39:1; the contents of active silicon and active aluminum in the activated kaolin are 93wt% and 95wt% of the silicon source and aluminum source in natural silica-alumina minerals, respectively;

[0311] 2) 9.8 g of activated kaolin was crushed in a crusher for 2 min (output power 800 W, speed 26000 r / min), then ball-milled in a ball mill at a speed of 300 rpm for 60 min, and then crushed and sieved to less than 200 mesh;

[0312] 3) Preparation of reactant gel

[0313] Using sodium hydroxide and potassium hydroxide as the second alkali source, 0.38g of sodium hydroxide and 0.18g of potassium hydroxide were dissolved in deionized water under stirring, and then the mechanically treated activated kaolin was added, and the mixture was aged at 60°C for 2h, and then white carbon black was added, and the mixture was aged at 60°C for 4h to obtain a reactant gel;

[0314] The molar ratio of sodium hydroxide to the second alkali source is 0.75:1; the molar ratio of the alkali source, silicon source, aluminum source and water in the reactant gel is 7:20:1:1800;

[0315] 4) Preparation of molecular sieves

[0316] The reactant gel was placed at 170°C for dynamic crystallization for 18 hours. After the crystallization was completed, it was cooled by 20-30°C, washed with deionized water until neutral, and dried at 120°C for 3 hours to obtain a molecular sieve.

[0317] Comparative Example 6

[0318] 1) Preparation of activated natural silica-alumina minerals

[0319] Sodium hydroxide and potassium hydroxide are used as the first alkali source, and kaolin is activated by a sub-molten salt activation method. The specific steps are: 1.8g of sodium hydroxide, 12.1g of potassium hydroxide, and 60g of deionized water are mixed and added into a polytetrafluoroethylene activation kettle, 10g of kaolin is added under stirring, and the activation kettle is placed in an oven at 250°C for activation for 3h to obtain activated kaolin; the activated kaolin is crushed and sieved to less than 200 meshes;

[0320] The molar ratio of sodium hydroxide to the first alkali source is 0.07:1; the mass ratio of the first alkali source to kaolin is 1.39:1; the contents of active silicon and active aluminum in the activated kaolin are 92wt% and 94wt% of the silicon source and aluminum source in natural silica-alumina minerals, respectively;

[0321] 2) Preparation of the second mixture

[0322] 9.8 g of activated kaolin and 1.1 g of SSZ-13 seed crystals were mixed to obtain a first mixture; the first mixture was crushed in a crusher for 2 min (output power 800 W, speed 26000 r / min), and then ball-milled at a speed of 300 rpm for 60 min to obtain a second mixture; the second mixture was crushed and sieved to less than 200 mesh;

[0323] wherein the crystallinity of the SSZ-13 seed crystals in the second mixture is 67% of the SSZ-13 seed crystals in the first mixture;

[0324] 3) Preparation of reactant gel

[0325] Using sodium hydroxide and potassium hydroxide as the second alkali source, 0.61 g of sodium hydroxide and 0.02 g of potassium hydroxide were dissolved in deionized water under stirring, and then the second mixture was added, and aged at 60° C. for 2 h, and then white carbon black was added, and the aging was continued at 60° C. for 4 h to obtain a reactant gel;

[0326] The molar ratio of sodium hydroxide to the second alkali source is 0.97:1; the molar ratio of the alkali source, silicon source, aluminum source and water in the reactant gel is 7:20:1:1800; the mass ratio of the SSZ-13 seed crystal to the silicon source is 5:100;

[0327] 4) Preparation of molecular sieves

[0328] The reactant gel was placed at 170°C for dynamic crystallization for 18 hours. After the crystallization was completed, it was cooled by 20-30°C, washed with deionized water until neutral, and dried at 120°C for 3 hours to obtain a molecular sieve.

[0329] Comparative Example 7

[0330] 1) Preparation of activated natural silica-alumina minerals

[0331] Sodium hydroxide and potassium hydroxide are used as the first alkali source, and kaolin is activated by a sub-molten salt activation method. The specific steps are: 8.0g of sodium hydroxide, 5.9g of potassium hydroxide, and 60g of deionized water are mixed and added into a polytetrafluoroethylene activation kettle, 10g of kaolin is added under stirring, and the activation kettle is placed in an oven at 250°C for activation for 3h to obtain activated kaolin; the activated kaolin is crushed and sieved to less than 200 meshes;

[0332] The molar ratio of sodium hydroxide to the first alkali source is 0.66:1; the mass ratio of the first alkali source to kaolin is 1.39:1; the contents of active silicon and active aluminum in the activated kaolin are 93wt% and 95wt% of the silicon source and aluminum source in natural silica-alumina minerals, respectively;

[0333] 2) Preparation of the second mixture

[0334] 9.8 g of activated kaolin and 1.1 g of SSZ-13 seed crystals were mixed to obtain a first mixture; the first mixture was crushed in a crusher for 2 min (output power 800 W, speed 26000 r / min), and then ball-milled in a ball mill at a speed of 300 rpm for 60 min to obtain a second mixture; the second mixture was crushed and sieved to less than 200 mesh;

[0335] wherein the crystallinity of the SSZ-13 seed crystals in the second mixture is 67% of the SSZ-13 seed crystals in the first mixture;

[0336] 3) Preparation of reactant gel

[0337] Using sodium hydroxide and potassium hydroxide as the second alkali source, 0.23 g of sodium hydroxide and 0.4 g of potassium hydroxide were dissolved in deionized water under stirring, and then the second mixture was added, aged at 60° C. for 2 h, and then white carbon black was added, and the aging was continued at 60° C. for 4 h to obtain a reactant gel;

[0338] The molar ratio of sodium hydroxide to the second alkali source is 0.45:1; the molar ratio of the alkali source, silicon source, aluminum source and water in the reactant gel is 7:20:1:1800; the mass ratio of the SSZ-13 seed crystal to the silicon source is 5:100;

[0339] 4) Preparation of molecular sieves

[0340] The reactant gel was placed at 170°C for dynamic crystallization for 18 hours. After the crystallization was completed, it was cooled by 20-30°C, washed with deionized water until neutral, and dried at 120°C for 3 hours to obtain a molecular sieve.

[0341] Comparative Example 8

[0342] 1) Preparation of activated natural silica-alumina minerals

[0343] Sodium hydroxide and potassium hydroxide are used as the first alkali source, and kaolin is activated by a sub-molten salt activation method. The specific steps are: 8.0g of sodium hydroxide, 5.9g of potassium hydroxide, and 60g of deionized water are mixed and added into a polytetrafluoroethylene activation kettle, 10g of kaolin is added under stirring, and the activation kettle is placed in an oven at 250°C for activation for 3h to obtain activated kaolin; the activated kaolin is crushed and sieved to less than 200 meshes;

[0344] The molar ratio of sodium hydroxide to the first alkali source is 0.66:1; the mass ratio of the first alkali source to kaolin is 1.39:1; the contents of active silicon and active aluminum in the activated kaolin are 93wt% and 95wt% of the silicon source and aluminum source in natural silica-alumina minerals, respectively;

[0345] 2) Preparation of the second mixture

[0346] 9.8 g of activated kaolin and 1.1 g of SSZ-13 seed crystals were mixed to obtain a first mixture; the first mixture was crushed in a crusher for 2 min (output power 800 W, speed 26000 r / min), and then ball-milled at a speed of 300 rpm for 10 min to obtain a second mixture; the second mixture was crushed and sieved to less than 200 mesh;

[0347] wherein the crystallinity of the SSZ-13 seed crystals in the second mixture is 85% of the SSZ-13 seed crystals in the first mixture;

[0348] 3) Preparation of reactant gel

[0349] Using sodium hydroxide and potassium hydroxide as the second alkali source, 0.38 g of sodium hydroxide and 0.18 g of potassium hydroxide were dissolved in deionized water under stirring, and then the second mixture was added, and the mixture was aged at 60° C. for 2 h, and then white carbon black was added, and the mixture was aged at 60° C. for 4 h to obtain a reactant gel;

[0350] The molar ratio of sodium hydroxide to the second alkali source is 0.75:1; the molar ratio of the alkali source, silicon source, aluminum source and water in the reactant gel is 7:20:1:1800; the mass ratio of the SSZ-13 seed crystal to the silicon source is 5:100;

[0351] 4) Preparation of molecular sieves

[0352] The reactant gel was placed at 170°C for dynamic crystallization for 18 hours. After the crystallization was completed, it was cooled by 20-30°C, washed with deionized water until neutral, and dried at 120°C for 3 hours to obtain a molecular sieve.

[0353] Comparative Example 9

[0354] This comparative example takes the synthesis method in the background technology (Document (Microporous and Mesoporous Materials, 2014, 196: 341-348)) as an example, and the specific synthesis steps are as follows: 0.8g NaOH and 0.56g KOH are dissolved in deionized water, and 0.41g sodium aluminate is added and stirred continuously until it is completely dissolved, and then 2.4g white carbon black is added to the reaction solution. Under stirring conditions, aging is continued at room temperature for 4h. Finally, SSZ-13 molecular sieve seeds are added to the reaction solution (the amount of SSZ-13 added is equivalent to 20wt.% of the total mass of the silicon source of the system), and stirring is continued for 0.5h to obtain a reactant gel. The molar ratio of the components of the reactant gel is 6Na2O:2.4K2O:20SiO2:1Al2O3:1900H2O, and the crystallization conditions are: dynamic crystallization at 170°C for 18h to obtain a molecular sieve.

[0355] Comparative Example 10

[0356] 1) Preparation of activated natural silica-alumina minerals

[0357] Sodium hydroxide and potassium hydroxide are used as the first alkali source, and kaolin is activated by a sub-molten salt activation method. The specific steps are: 4.9g of sodium hydroxide, 3.5g of potassium hydroxide, and 60g of deionized water are mixed and added into a polytetrafluoroethylene activation kettle, 10g of kaolin is added under stirring, and the activation kettle is placed in an oven at 250°C for activation for 3h to obtain activated kaolin; the activated kaolin is crushed and sieved to less than 200 meshes;

[0358] The molar ratio of sodium hydroxide to the first alkali source is 0.66:1; the mass ratio of the first alkali source to kaolin is 0.84:1; the contents of active silicon and active aluminum in the activated kaolin are 81 wt% and 77 wt% of the silicon source and aluminum source in the natural silica-alumina mineral, respectively;

[0359] 2) Preparation of the second mixture

[0360] 9.8 g of activated kaolin and 1.1 g of SSZ-13 seed crystals were mixed to obtain a first mixture; the first mixture was crushed in a crusher for 2 min (output power 800 W, speed 26000 r / min), and then ball-milled in a ball mill at a speed of 300 rpm for 60 min to obtain a second mixture; the second mixture was crushed and sieved to less than 200 mesh;

[0361] wherein the crystallinity of the SSZ-13 seed crystals in the second mixture is 67% of the SSZ-13 seed crystals in the first mixture;

[0362] 3) Preparation of reactant gel

[0363] Using sodium hydroxide and potassium hydroxide as the second alkali source, 0.42 g of sodium hydroxide and 0.20 g of potassium hydroxide were dissolved in deionized water under stirring, and then the second mixture was added, and the mixture was aged at 60° C. for 2 h, and then white carbon black was added, and the mixture was aged at 60° C. for 4 h to obtain a reactant gel;

[0364] The molar ratio of sodium hydroxide to the second alkali source is 0.75:1; the total molar ratio of the alkali source, silicon source, aluminum source and water in the reactant gel is 7:20:1:1800; the mass ratio of SSZ-13 seed crystals to silicon source is 5:100;

[0365] 4) Preparation of SSZ-13 molecular sieve

[0366] The reactant gel was placed at 170°C for dynamic crystallization for 18 hours. After the crystallization was completed, it was cooled to 20-30°C, washed with deionized water until neutral, and dried at 120°C for 3 hours to obtain SSZ-13 molecular sieve.

[0367] Test Example 1

[0368] The crystallization of the molecular sieves prepared in Examples 1-14 and Comparative Examples 1-10 of the present invention was characterized by XRD spectra. Figure 2a and Figure 2b .

[0369] The crystallinity of the molecular sieve prepared in Comparative Example 9 was set to 100%, and the ratio of the sum of the peak areas when 2θ was 9.5°, 14°, 16°, 18°, 21°, 25°, 26.5° and 31° in the XRD spectra of the SSZ-13 molecular sieves prepared in Examples 1-14 of the present invention and Comparative Examples 8-10 was calculated to obtain the relative crystallinity of the SSZ-13 molecular sieves prepared in Examples 1-14 of the present invention. The results are shown in Table 1.

[0370] Table 1

[0371]

[0372]

[0373] according to Figure 2a and Figure 2b It can be seen that the SSZ-13 molecular sieves prepared in Examples 1-14 and Comparative Examples 8-10 are pure phases without impurity crystals. The molecular sieves of Comparative Examples 1, 2, and 3 have a characteristic diffraction peak of mordenite at 9.77°, which is a mixed crystal of mordenite and SSZ-13. The molecular sieve of Comparative Example 4 is an amorphous substance and fails to synthesize SSZ-13 molecular sieves. Comparative Example 5 is PHI zeolite. The products of Comparative Examples 6 and 7 are mixed crystals of SSZ-13 and PHI type molecular sieves. The products of Comparative Examples 8, 9, and 10 are SSZ-13 molecular sieves. According to Table 1, the relative crystallinity of the SSZ-13 molecular sieves prepared in Examples 1-14 of the present invention is not less than 102.6%, which is significantly higher than Comparative Examples 8-10.

[0374] Compared with Comparative Examples 1, 2, 3 and 5, Examples 1-14 all obtained pure phase SSZ-13 molecular sieves, which indicates that the composition of the first alkali source, the composition of the second alkali source, whether mechanical treatment is performed, and whether seed crystals are added for activating natural silica-alumina minerals determine the crystalline structure of the product. By controlling the composition of the first alkali source, the second alkali source, the method of mechanical treatment and the amount of seed crystals added, a pure phase SSZ-13 molecular sieve can be obtained.

[0375] Compared with Examples 9 and 10, the SSZ-13 molecular sieve of Example 2 has a higher degree of crystallinity, which indicates that controlling the particle size of the activated natural silica-alumina mineral to be less than 200 mesh and controlling the molar ratio of sodium hydroxide to the first alkali source in the first alkali source to (0.6-0.9):1 are both beneficial to obtaining a SSZ-13 molecular sieve with higher crystallinity.

[0376] Compared with Example 13, the SSZ-13 molecular sieve prepared in Example 9 has higher crystallinity, which indicates that the size of the second mixture is also an important factor affecting the crystallinity of the SSZ-13 molecular sieve. Controlling the particle size of the second mixture to be less than 200 mesh is conducive to the synthesis of SSZ-13 molecular sieve with higher crystallinity.

[0377] Compared with Example 14, the SSZ-13 molecular sieve prepared in Example 6 has higher crystallinity, which indicates that when the second mixture is prepared by kneading and extrusion, the mass ratio of water to the first mixture will affect the crystallinity of the SSZ-13 molecular sieve.

[0378] Test Example 2

[0379] The microstructure of SSZ-13 molecular sieve was characterized by SEM images.

[0380] Figure 3a , Figure 3b , Figure 3c , Figure 3d The SEM images of the molecular sieves prepared in Example 1 of the present invention and Comparative Examples 1-3 are shown in sequence. The results show that compared with Comparative Examples 1-3, the product prepared in Example 1 of the present invention is a nanoscale SSZ-13 molecular sieve with a cubic morphology, while in Comparative Examples 1-3, although it also has a cubic morphology, the size of the cube is significantly larger, and there are thin rod-shaped impurities, which indicates that the SSZ-13 molecular sieve prepared in Comparative Examples 1-3 is a non-pure phase molecular sieve, which also contains mordenite, while the molecular sieve prepared in Example 1 of the present invention is a pure phase SSZ-13 molecular sieve.

[0381] Test Example 3

[0382] The nitrogen adsorption-desorption isotherm curve was measured by a high-performance fully automatic gas adsorption instrument, thereby obtaining the specific surface area, micropore volume and mesopore volume of the SSZ-13 molecular sieve prepared in Example 3 and Example 10 of the present invention.

[0383] Figure 4a , Figure 4b The nitrogen adsorption and desorption isotherms of the SSZ-13 molecular sieves prepared in Example 3 and Example 10 of the present invention are shown in Figure 1. According to calculation, the specific surface area of ​​the SSZ-13 molecular sieve obtained in Example 3 of the present invention reaches 289 m 2 / g, micropore volume is 0.080cm 3 / g, and the mesopore volume is 0.214cm 3 / g; the specific surface area obtained in Example 10 reaches 283m 2 / g, micropore volume is 0.074cm 3 / g, and the mesopore volume is 0.178cm 3 / g;

[0384] Since the crystallinity of the SSZ-13 molecular sieves prepared in the remaining embodiments of the present invention is higher than that of Example 10, when Example 10 has a higher micro-mesopore volume and micro-mesopore specific surface area, the micro-mesopore volume and micro-mesopore specific surface area of ​​the remaining embodiments are relatively higher. Therefore, the SSZ-13 molecular sieves obtained in the present invention have a relatively excellent pore structure, which is beneficial for separating CO2 / CH4 and purifying nitrogen oxides in automobile exhaust.

[0385] Test Example 4

[0386] The present invention uses the breakthrough curve to characterize the CO2 / CH4 gas separation effect of the SSZ-13 molecular sieve synthesized in Example 1. The results are shown in Figure 5 Specifically: 1.0 g of the SSZ-13 molecular sieve synthesized in Example 1 was loaded into a penetration column with an inner diameter of 4.0 mm and a sample length of 97 mm, and then placed at 300°C for degassing for 3 h, with He as the purge gas and a flow rate of 5 mL / s. After the degassing treatment was completed, the temperature was lowered to 25°C, and after the temperature was constant, a CO2 / CH4 mixed gas (volume concentration of 50% / 50%) was introduced at a gas flow rate of 5 mL / s, and the gas concentration at the outlet of the penetration column was recorded by mass spectrometry.

[0387] according to Figure 5 It can be seen that when the SSZ-13 molecular sieve prepared in Example 1 of the present invention is used for CO2 / CH4 gas separation, the CH4 penetration time is extremely short and the CO2 penetration time is as long as 1500 seconds, which shows that the synthesized SSZ-13 molecular sieve can achieve efficient separation of CO2 and CH4 gases.

[0388] Test Example 5

[0389] 1) Automobile exhaust NO x Preparation of the remover

[0390] Prepare 0.1 M copper sulfate solution;

[0391] The SSZ-13 molecular sieve synthesized in Example 1 was mixed with a copper sulfate solution at a solid-liquid ratio of 1:20, ion exchanged at 80°C for 2h, washed with deionized water until neutral, dried at 110°C, and then calcined at 550°C for 2h to obtain automobile exhaust NO x Remover.

[0392] 2) Automobile exhaust NO x NH3-SCR reaction of the remover

[0393] NO xThe removal agent was tableted, crushed and sieved to obtain particles of 20-40 mesh size. The experiment was carried out in a fixed bed quartz microreactor with an inner diameter of 7 mm. The reactant gas mixture consisted of: NO 500ppm, NH3500ppm, O2 5%, N2 as the balance gas, and the space velocity was 120000h -1 The reaction temperature is 150-600°C, and the concentrations of NO and N2O in the outlet gas mixture are measured using a flue gas analyzer and a Fourier transform infrared spectrometer.

[0394] Figure 6a The conversion rate of nitrogen monoxide when the SSZ-13 molecular sieve obtained in Example 1 of the present invention is used for NH3-SCR; Figure 6b The nitrogen selectivity of the SSZ-13 molecular sieve obtained in Example 1 of the present invention when used for NH3-SCR.

[0395] according to Figure 6a and Figure 6b It can be seen that within the temperature range of 150-600°C, the conversion rate of NO is greater than 80%, and the selectivity of N2 is greater than 98%, which shows that the SSZ-13 molecular sieve prepared by the present invention is suitable for preparing automobile exhaust NO x After removing the agent, it has a wider active window temperature and higher NO selectivity.

[0396] In order to make the purpose, technical solution and advantages of the present invention clearer, the above-mentioned technical solution of the present invention is clearly and completely described in combination with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, but not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A method for preparing SSZ-13 molecular sieve, characterized in that: The following steps are included: 1) activating the natural silica-aluminum mineral using a first alkali source to obtain an activated natural silica-aluminum mineral; 2) adding SSZ-13 seed crystals to the activated natural silica-alumina mineral to obtain a first mixture, and mechanically treating the first mixture to obtain a second mixture; wherein the crystallinity of the SSZ-13 seed crystals in the second mixture is 30% to 80% of the crystallinity of the SSZ-13 seed crystals in the first mixture; 3) mixing the second mixture with a silicon source, a second alkali source and water to obtain a reactant gel; 4) subjecting the reactant gel to aging treatment and crystallization treatment in sequence to obtain SSZ-13 molecular sieve; Wherein, the contents of active silicon and active aluminum in the activated natural silica-aluminum mineral are not less than 90wt% of the silicon source and aluminum source in the natural silica-aluminum mineral respectively; The first alkali source and the second alkali source include sodium hydroxide, potassium hydroxide and / or cesium hydroxide; In the first alkali source, the molar ratio of sodium hydroxide to the first alkali source is (0.2-0.9):1; In the second alkali source, the molar ratio of sodium hydroxide to the second alkali source is (0.5-0.92):1; The mass ratio of the SSZ-13 seed crystal to the silicon source is (0.1-10.0):100; In the reactant gel, the molar ratio of the alkali source, the silicon source, the aluminum source and water is (7.0-15.5): (10-120): 1: (1600-2200).

2. The preparation method according to claim 1, characterized in that: In step 1), the mass ratio of the first alkali source to the natural silica-alumina mineral is (1.2-1.8):1; and / or, In the first alkali source, the molar ratio of sodium hydroxide to the first alkali source is (0.6-0.9):

1.

3. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the SSZ-13 seed crystal to the silicon source is (0.1-3.0):

100.

4. The preparation method according to any one of claims 1 to 3, characterized in that Step 3) further includes adding TMAdaOH to the system including the second mixture, a silicon source, an alkali source and water, wherein the molar ratio of the TMAdaOH to the silicon source is (0-0.01):

1.

5. The preparation method according to any one of claims 1 to 4, characterized in that: In step 2), the mechanical treatment includes a first mechanical treatment and a second mechanical treatment, and the first mechanical treatment includes a crushing treatment; The second mechanical treatment includes at least one of grinding, mechanical ball milling, mechanical kneading, and extrusion molding, and when the second mechanical treatment includes the mechanical kneading and / or the extrusion molding, water is added to the first mixture, and the mass ratio of the water to the first mixture is (5-20):

100.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The size of the activated natural silica-alumina mineral is less than 200 mesh; and / or, The second mixture has a size of less than 200 mesh.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The aging treatment temperature is 50-70°C and the time is 2-8h; and / or, The crystallization treatment is dynamic crystallization, and the temperature of the dynamic crystallization is 150-180° C. and the time is 12-72 hours.

8. An SSZ-13 molecular sieve, characterized in that: The method is prepared by the method according to any one of claims 1 to 7.

9. A CO2 / CH4 separation agent, characterized in that: Comprising the SSZ-13 molecular sieve described in claim 8.

10. A kind of automobile exhaust NO x A stripping agent, characterized in that The method is obtained by subjecting the SSZ-13 molecular sieve described in claim 8 to copper ion exchange.

Citation Information

Patent Citations

  • NO120000B

  • use of calcium silicate granules or powder with a microporous structure as an oleophilic absorbent or absorbent

    NO150600B

  • Preparation method and application of mesoporous Fe-Cu-SSZ-13 molecular sieve

    CN109382137A

  • Method for preparing SSZ-13 molecular sieve from coal ash

    CN110040743A